Analysis of Aquifer Pumping Test Data to Determine Deep Groundwater Security in Southeastern Bangladesh - Zahid, Anwar; Islam, Farhana; Rashidul Hassan, M.; Islam, Kamrul; Ahmed, Nur (JNRD - Journal of Natural Resources and Development, 2018)
In southeastern Bangladesh, where water quality in the upper aquifers is a serious constraint, future development will likely be confined to deep fresh groundwater. Owing to the importance and pervasive use of deep groundwater, the sustainability of water use has received extensive attention. However, excessive extraction from deep aquifers may pose a threat to the storage as well as the quality of water due to the high susceptibility to salinization and arsenic contamination from upper aquifers. Hence, determining the extension of aquifer units and the characterizing aquifer sediments are very important to ensure sustainable development and management of limited fresh groundwater resources. The study area extends over six districts of the southeastern coastal region of Bangladesh. In order to assess and monitor deep fresh groundwater potential in the study area, aquifer pumping tests were performed at six locations with up to 72 h of constant-discharge prior to recovery. Different methods were used to analyze the drawdown and recovery data considering aquifers as confined or leaky-confined. Based on transmissivity values it was found that the studied deep aquifers have moderate to high potential for potable water supply. However, this deep fresh groundwater may not be safe for a longer period where upper aquifer units contain saline groundwater and where there is no significant aquitard encountered above or below the deep aquifer. Irrigation extraction of the deep groundwater is not recommended.